2022
DOI: 10.1021/acsanm.2c02976
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Cross-Linked DNA Origami Nanostructures for Drug Delivery Applications

Abstract: Biocompatible DNA origami nanostructures (DONs) attract significant interest as potential targeted drug carriers. Their sensitivity to various environmental triggers is beneficial as a drug release or decomposition mechanism, but it also hinders their stability; therefore, they require some extent of cross-linking. Using cisplatin, we demonstrate that a molecule can both act as a therapeutic and cross-linking agent for DONs. In this work, triangular two-dimensional DONs are loaded with ∼1000 cisplatin molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…To prepare the self-assembled DNA nanogel, herring sperm DNA (hsDNA) segments (<50 bp) were selected as a model DNA since it is readily available and cost-effective and widely used for studying drug–DNA interactions ( Sirajuddin et al, 2013 ; Xiong et al, 2021 ). Cisplatin, a common chemotherapeutic drug that could also act as a crosslinker to build different nanoparticles ( Li et al, 2014 ; Zhang and Tung, 2017a ; Wang et al, 2021 ; Sala et al, 2022 ), was utilized to construct the DNA nanogel, as previously demonstrated ( Zhang and Tung, 2017b ). A simple mixing of cisplatin, TB, and hsDNA, followed by a heating and cooling process, generated the DNA/TB NG ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the self-assembled DNA nanogel, herring sperm DNA (hsDNA) segments (<50 bp) were selected as a model DNA since it is readily available and cost-effective and widely used for studying drug–DNA interactions ( Sirajuddin et al, 2013 ; Xiong et al, 2021 ). Cisplatin, a common chemotherapeutic drug that could also act as a crosslinker to build different nanoparticles ( Li et al, 2014 ; Zhang and Tung, 2017a ; Wang et al, 2021 ; Sala et al, 2022 ), was utilized to construct the DNA nanogel, as previously demonstrated ( Zhang and Tung, 2017b ). A simple mixing of cisplatin, TB, and hsDNA, followed by a heating and cooling process, generated the DNA/TB NG ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…There are several strategies for strengthening DNA, such as adding chemicals that can enhance DNA mechanics. For example, crosslinking molecules can improve the thermal stability of DNA structures, [126][127][128][129] and will likely enhance the stiffness and mechanical stability. This mechanical enhancement has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from photo-crosslinking, chemical crosslinking methods also have been developed. 128,129 Shih et al used polyethylene glycol (PEG) modified oligolysine-coated DNA nanostructures. With addition of glutaraldehyde, the structures can be crosslinked and show 400-fold higher resistance to nuclease as well as improved stability in low-salt environments.…”
Section: Other Related Methods For Reinforcementmentioning
confidence: 99%
“…Chemical crosslinking methods also have been developed for structural reinforcement. 170,171 Anastassacos et al used polyethylene glycol (PEG) modied oligolysines for coating DNA nanostructures. With addition of glutaraldehyde, the structures were crosslinked and showed 400-fold higher resistance to nuclease as well as improved stability in low-salt environments.…”
Section: Structural Reinforcementmentioning
confidence: 99%